Dodine ve Chorus pestisistlerinin Cydonia oblonga Miller (ayva) ve Cerasus vulgaris Miller (vişne) bitkilerinin polen performansı üzerine etkileri - Topdemir, Aykut; Gür, Nazmi; Demir, Zümre (My University, 2015)
The use of pesticides are inevitable today. However, when using peticides it should be evaluated together both protection of products against disease, pest and weed, and negative effects of product’s on people and environment. Our aim in this study, to investigate the effects of widely used dodine and chrous pesticides on the in vitro germination and tube length of Cydonia oblonga (quince) and Cerasus vulgaris Miller (cherry) plant’s pollen. In this study that Brewbaker-Kwack medium used as pollen culture medium, pollens were cultivated in 2 for each 50 µl of culture medium which located on each slide. The slides which made on pollen cultvation by this way were placed on glass rods in the petri dish furnished with wet filter paper. After the lid of petri dishes closed, they incubated for 3 hours at 22±1 oC. In experimental group, it was added that 50 µl pesticides with different concentrations in each of these drops, and same volume of water in the control group. It was fixed by dripping a drop of 10% ethanol in culture medium on the slide which removed from the incubator at the end of this time. After fixation process lamellae closed, germination percentage and tube lengths were measured under light microscope according to method described in Shivanna and Rangaswamy. In accordance with the obtained results, Chorus pesticide, diluted from field dust by ½ ratio was the most affecting pesticide of the germination rate of cherry pollen and tube length, however, Dodine pesticide at the same concentrations and parameters much more affected quince plant respectively. 1?32 concentration of both pesticides in both plants had the least effect on pollen germination and tube length ratio.

Günümüzde pestisitlerin kullanılması kaçınılmazdır. Ancak pestisit kullanılırken, hem ürünün hastalık, zararlı ve yabancı otlara karşı korunması hem de insan ve çevreye olumsuz etkileri birlikte değerlendirilmelidir. Bu çalışmadaki amacımız, yaygın olarak kullanılan dodine ve chorus pestisitlerinin Cydonia oblonga Miller (ayva) ve Cerasus vulgaris Miller (vişne) bitkisi polenlerinin in vitro çimlenmesi ve tüp uzunluğu üzerine etkilerini araştırmaktır. Polen kültür ortamı olarak Brewbaker-Kwack besiyerinin kullanıldığı çalışmada, polenler her lam üzerinde bulunan 2 şer adet 50µl lik kültür ortamına ekilmiştir. Bu şekilde üzerine polen ekimi yapılan lamlar, ıslak filtre kağıdı ile döşenmiş petri kutusu içerisindeki cam çubuklar üzerine yerleştirilmiştir. Petri kutularının kapağı kapatıldıktan sonra 22±1 o C’lik inkübatörde 3 saat inkübe edilmiştir. Deney grubunda bu damlaların her birine 50’şer µl farklı konsantrasyonlarda pestisit, kontrol grubunda ise aynı hacimde su eklenmiştir. Bu sürenin sonunda inkübatörden çıkarılan lamların üzerindeki kültür ortamlarına birer damla %10’ luk etanol damlatılarak fikse edilmiştir. Fiksasyon işleminin ardından lamel kapatılarak, ışık mikroskobu altında Shivanna ve Rangaswamy’da anlatılan yönteme göre polenlerin çimlenme yüzdeleri ile tüp uzunlukları ölçülmüştür. Elde edilen sonuçlara göre, tarla dozundan ½ oranında seyreltilmiş chorus pestisiti, vişne polenlerinin çimlenme oranını ve polen tüp uzunluğunu en fazla etkileyen pestisit olurken, ayva bitkisini yine aynı konsantrasyon ve parametrelerdeki dodine pestisiti daha fazla etkilenmiştir. Her iki bitki içinde her iki pestisitin ’lik konsantrasyonu polen çimlenme ve tüp uzunluğunu en az etkileyen oran olmuştur.
Cydonia oblonga Miller of Dodi and Chorus Pesticides (Quince) and Cerasus vulgaris Miller (Cherry) effects of plant pollen performance
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pestisit; Cydonia oblonga Miller (ayva); Cerasus vulgaris Miller (vişne); Polen çimlenmesi; Polen tüpü gelişimi; Pesticide; Pollen germination; Pollen tube growth